1272. A Routine, HIV and HCV Testing and Treatment Program in a Large, Multi-Campus Emergency Department Finds High Prevalence of Acute HIV and Chronic Hepatitis C. (26th November 2018) - Anson, Ryan; Hall, Christopher; Ivans, Erica; Vassily, Kara; Shaieb, Annette; Berrol, Ronn; Potts, Brian; Bures, Erin
Abstract: Background: One in seven people living with HIV in the United States are unaware of their serostatus. Approximately 11, 280 annual HIV infections (30.2%) are caused by this subset of individuals (CDC, 2017). In addition, acute HCV infections have nearly tripled since 2011, with many states seeing a dramatic increase in incidence among younger people outside the birth cohort (CDC, 2017). Because many individuals still use emergency departments (EDs) for their healthcare needs, these institutions play an increasingly important role in screening patients for HIV and HCV and linking them to medical services. Routine, opt-out testing initiatives are particularly effective at identifying new cases of HIV and HCV that could have otherwise been missed by a risk-based approach to screening. Methods: In early May 2017, physicians and advanced practice nurses from Sutter Health's Alta Bates Summit Medical Center (ABSMC) and a nearby outpatient HIV clinic implemented a routine HIV and HCV screening program at the hospital's large, two-campus ED system in Oakland, CA. ED medical directors created a Nursing Standardized Procedure (NSP) to allow registered nurses (RNs) to independently order both blood tests using an automated, best practice authority (BPA) screen in the electronic health record (EHR) of any patient who met CDC-defined age criteria for testing. Results: Of the 6, 315 people screened for HIV between May 1, 2017 and March 31, 2018, 43 (0.7%) patients tested positive. Twelve (57%) of the 21 patients found to have a new HIV diagnosis also had symptomatic, acute HIV infection (AHI). All 12 patients with AHI initiated anti-retroviral therapy (ART) within five to 96 hours of their preliminary positive test result. Of the 5, 820 patients screened for HCV, 424 (7.3%) were anti-HCV positive, while 185 (3.2%) patients had chronic infection. Thirty-nine percent of chronic HCV cases were among younger patients born before 1965. All patients with HIV or chronic HCV were referred to medical care at East Bay Advanced Care (EBAC). Conclusion: An automated, routine HIV-HCV testing program integrated into standard nursing workflow at a community ED resulted in the timely screening, diagnosis, and treatment of many patients with acute HIV, and identified a high prevalence of chronic HCV infections among younger patients. Disclosures: R. Anson, Frontline of Communities in the United States (Gilead, Inc.): Grant Investigator, Grant recipient. C. Hall, Frontline of Communities in the United States (Gilead, Inc.): Grant Investigator, Grant recipient.